Traffic organization and transport forecast for the proposed Otwock – Karczew railway line - Szymon Klemba (Przegląd Komunikacyjny)
Abstract: The article concerns the concept of building a new railway line between Otwock and Karczew. Proposed variants of the railway line are presented and the organization of railway traffic for each variant presented in the concept is proposed. It is assumed that the existing route of Fast Urban Railway line would be extended or a new circle line would be launched. Transport forecasts were developed using the Polish Integrated Traffic Model. Results indicate that the proposed line has a large transport potential, and in the most developed variant, it would open up new travel opportunities around the Warsaw agglomeration.